Unmasking the Pandemic's Shadow: A Systematic Review of The Multifaceted Impact of COVID-19 Stigma in Asia - Yosephina Elizabeth Sumartini Gunawan; Leni Landudjama; Servasius To’o Jala Mulu; Irene Febriany Mamo Kitu; Maria Christina Endang Sukartiningsih; Dwi Febryanto; Guang-Hsing Liu; Yuliana Dafroyati (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
The COVID-19 pandemic has exacerbated stigma toward health workers, patients, and survivors while intensifying social inequalities through rising unemployment, poverty, and social exclusion. This systematic review examined literature from ProQuest, Science Direct, Google Scholar, and PubMed, focusing on the stigma of COVID-19 in Asia. Original research employing quantitative or qualitative methods was included for articles that published in 2020-2021, while review articles were excluded. Screening followed PRISMA guidelines, with data collection and analysis conducted from November 2021 to April 2022, resulting in 24 articles. Data extracted included titles, authors, publication years, participants, methods, findings, strengths, and limitations. Quality was assessed using JBI’s critical appraisal tools, and thematic analysis was performed using Braun and Clarke’s framework. The review identified three key themes: general characteristics of COVID-19 stigma, affected populations, and the multifaceted impacts. Stigma in Asia has led to widespread fear and discrimination against infected individuals, survivors, health workers, and vulnerable groups with significant psychological, spiritual, economic, and health repercussions. We recommend that the government raise public awareness to minimize misinformation by providing education about COVID-19 and efforts to address the impacts caused by stigma, as well as integrating anti-stigma measures into policies and expanding mental health services for those affected.